Influence of Geographic Access on Surgical Center Readmissions After Index Congenital Heart Surgery - Pinto, Nelangi M.; LuAnn Minich, L.; Yoo, Minkyoung; Floyd, Alisha; Wilkes, Jacob; VanDerslice, James; Yamauchi, Melissa; Nelson, Richard (The Journal of pediatrics, 2021)
To assess the impact of geographic access to surgical center on readmission risk and burden in children after congenital heart surgery. Children <6 years old at discharge after congenital heart surgery (Risk Adjustment for Congenital Heart Surgery-1 score 2-6) were identified using Pediatric Health Information System data (46 hospitals, 2004-2015). Residential distance from the surgery center, calculated using ZIP code centroids, was categorized as <15, 15-29, 30-59, 60-119, and ≥120 miles. Rurality was defined using rural–urban commuting area codes. Geographic risk factors for unplanned readmissions to the surgical center and associated burden (total hospital length of stay [LOS], costs, and complications) were analyzed using multivariable regression. Among 59 696 eligible children, 19 355 (32%) had ≥1 unplanned readmission. The median LOS was 9 days (IQR 22) across the entire cohort. In those readmitted, median total costs were $31 559 (IQR $90 176). Distance from the center was inversely related but rurality was positively related to readmission risk. Among those readmitted, increased distance was associated with longer LOS, more complications, and greater costs. Compared with urban patients, highly rural patients were more likely to have an unplanned readmission but had fewer average readmission days. Geographic measures of access differentially affect readmission to the surgery center. Increased distance from the center was associated with fewer unplanned readmissions but more complications. Among those readmitted, the most isolated patients had the greatest readmission costs. Understanding the contribution of geographic access will aid in developing strategies to improve care delivery to this population.